AUTOMATIC GENERATION OF ROAD INFRASTRUCTURE IN 3D FOR VEHICLE SIMULATORS - Adam Orlický (Acta Polytechnica CTU Proceedings)
One of the modern methods of testing new systems and interfaces in vehicles is testing in a vehicle simulator. Providing quality models of virtual scenes is one of tasks for driver-car interaction interface simulation. Nowadays, there exist many programs for creating 3D models of road infrastructures, but most of these programs are very expensive or canÂtt export models for the following use. Therefore, a plug-in has been developed at the Faculty of Transportation Sciences in Prague. It can generate road infrastructure by Czech standard for designing roads (CSN 73 6101). The uniqueness of this plug-in is that it is the first tool for generating road infrastructure in NURBS representation. This type of representation brings more exact models and allows to optimize transfer for creating quality models for vehicle simulators. The scenes created by this plug-in were tested on vehicle simulators. The results have shown that with newly created scenes drivers had a much better feeling in comparison to previous scenes.